Epizódok M. F. tanár úr életéből. Mérei porté
Filmed shortly before his death, the documentary is a portrait of Ferenc Mérei (1909-1986), the prominent figure of Hungarian clinical psychodiagnostics and psychotherapy. Péter Forgács